Implementation the Ethnoscience-Based Smart Module to Improve Students’ Patriotism - S. D. Ardianti; S. Wanabuliandari; A. B. Tanghal (Jurnal Pendidikan IPA Indonesia, 2023)
Patriotism begins to fade in the younger generation of Indonesians. The loss of patriotism will cause concern for the nation. Thus, there must be innovation in teaching to cultivate patriotism. The ethnoscience-based smart module helps students learn independently in a fun way and contributes to improving their patriotism. This study aims to analyze the improvement of students’ patriotism through implementing the ethnoscience-based smart module. This research used the research and development (R D) model by Borg and Gall. The research and development stages of ethnoscience-based smart modules included preliminary research, product development and validation, and product testing. The study was conducted in three primary schools in Kudus. The research design used in this study was a single-group pretest and posttest design. The data were analyzed using the N-gain test to determine the improvement of students’ patriotism. The results of the N-gain test show an increase in patriotism, with an average initial score of 50 increasing to an average final score of 80, and classically, the normalized gain value is 60% or 0.60, which means an increase in the medium category through the application of the ethnoscience-based smart module. Based on research results, it can be concluded that implementing an ethnoscience-based smart module can improve students’ patriotism in elementary schools.